2004
DOI: 10.1111/j.1443-1661.2005.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Useful Endoscopic Ultrasonography to Assess the Efficacy of Neoadjuvant Therapy for Advanced Esophageal Carcinoma: Based on the Response Evaluation Criteria in Solid Tumors

Abstract: Objective : The aim of the present study was to assess the usefulness of endoscopic ultrasonography (EUS) for evaluating the efficacy of neoadjuvant therapy for advanced esophageal carcinoma based on the Response Evaluation Criteria in Solid Tumors (RECIST). Patients and Methods : Sixty-two patients with advanced esophageal carcinoma underwent surgical resection after neoadjuvant therapy. The maximal tumor thickness was measured by EUS before and after neoadjuvant therapy, and the percent reduction was compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
(24 reference statements)
0
15
2
Order By: Relevance
“…Some used maximal crosssectional area reduction more than 50% as good response, 17,19,20 while others used maximal tumor thickness reduction more than 30% or 50%. 12,18 These studies had consistently found that tumor size reduction on EUS is predictive of pathological response on surgical specimen. However, the impact of EUS measurement on patient prognosis is less clear, 19,21 especially in patients with ESCC and treated by definitive CRT.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Some used maximal crosssectional area reduction more than 50% as good response, 17,19,20 while others used maximal tumor thickness reduction more than 30% or 50%. 12,18 These studies had consistently found that tumor size reduction on EUS is predictive of pathological response on surgical specimen. However, the impact of EUS measurement on patient prognosis is less clear, 19,21 especially in patients with ESCC and treated by definitive CRT.…”
Section: Discussionmentioning
confidence: 94%
“…Measurement of cross-sectional area was even more difficult in good CRT responders when most tumor masses disappeared and only circumferential esophageal wall thickening was present. Therefore, we measured maximal esophageal wall thickness as reported by Ota et al 12 Our finding that post-CRT esophageal wall thickness more than 8 mm predicted poor survival suggests that these patients should receive additional treatment to improve outcome. If observation is decided in such patients, then more frequent follow-up is necessary to identify tumor recurrence as early as possible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations